Effect of Interlamelar Composition on ZnAl Hydrotalcites: Synthesis and Characterization - Omonmhenle, Selina Ilunakan; Shannon, Ian James (European Scientific Journal, ESJ, 2019)
The preparation and characterisation of ZnAl hydrotalcites with varying interlamellar anions have been investigated. The synthesis was achieved through co-precipitation at low supersaturation, accompanied by hydrothermal curing at 110ËšC for 18h. A range of techniques such as XRD, XRF, FT-IR, TG-DTA, SEM, and surface area were utilised to investigate the effect that the varying of interlamellar anions impacted on the hydrotalcites. The x-ray diffraction and FT-IR data confirmed that the samples synthesised were hydrotalcites with the intercalation of various anions of interest. The nitrate hydrotalcite showed less stacking order with highest basal spacing, while the carbonate hydrotalcite showed smallest unit cell, more regular stacked sheets, and denser nanoparticles. Thermal results are identical in all hydrotalcite studied but with variance in the temperature of the decomposition stages. Suraface area and the scanning electron microscopy analysis demonstrated that the composition of interlamella region influences the structure and properties of the synthesised hydrotalcites.